Study Effect of Some Pakistan Oil Isolation of Yeast Candida albicans causing oral thrush children Who Visit Women Hospital and Children in Diwaniya - Nada Ahmed Fairooz 1 , Huda Ahmed Fairooz2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The aim of the study was to evaluate some of the essential oils of the candida albicans yeast causingcandidaiasis in children referred to the women hospital and children. The study included 108 oral swabsfrom infants with candidiasis ,all samples were diagnosed by diagnostic methods and after initial isolationof candida albicans 37.5% followed by species C.tropicalis 30% ,C.parapsilosis 12.38% as for C.kruseiand C.glabrata they were 9.4% .the results of the agar well diffusion method showed that the nigella sativaoil was the most inhibited followed by cinnamon oil ,while garlic oil was the least inhibited compared withthe nystatin.